Penggunaan Pestisida Nabati Ekstrak Daun Pepaya (Carica Papaya L.) pada Tanaman Kacang Panjang (Vigna Sinensis L.) untuk Mengurangi Dampak Pencemaran Lingkungan di Desa Gunung Selamat, Kec. Bilah Hulu, Kab. Labuhanbatu - Jujuaningsih Jujuaningsih; Khairul Rizal; Yudi Triyanto; Widya Lestari; Dahrul Aman Harahap (Universitas Mataram, 2021)
Vegetable pesticides are pesticides whose active ingredients come from plants and other organic materials that control pest attacks on plants, containing many bioactive compounds such as phenolic, alkaloid compounds and also other secondary chemical substances. Papayas are plants originating from Central America. Papaya can grow well in areas that are in tropical climates. Some of the ingredients contained in papaya leaves include papain enzymes, flavonoids, alkaloids, saponins, and tannis. All of the content contained in papaya leaves, the papain enzyme is the most abundant chemical content in papaya leaves because it comes from papaya sap.